2020
DOI: 10.1039/d0ma00173b
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer induced magnetic ordering of metal-cyanide magnets

Abstract: Solution synthesis of molecular cyanide magnets via FeSe template is promoted by thermal activation, where TCNE molecules substitute Se atoms in two-dimensional FeSe framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The advent of two-dimensional (2D) magnetic materials has attracted growing attention ranging from magnetics to quantum physics, resulting from the dimensionality and size effects on charge and spin correlation phenomena. However, most 2D magnetic materials have been focused on a few mother compounds exhibiting inherent 2D layer structures . To expand the diversity in chemical compositions and magnetic interactions at the 2D scale, it is highly desirable to create a universal strategy to artificially create 2D magnetic materials, particularly 2D molecular magnets with a variety of material groups and full tunability by external stimuli. The crystal structure transformation has been largely recognized as a key enabler for materials discovery. However, the structural transformations often occur between different lattice packings in the same dimensionality and have not been shown for the dimensionality transformation.…”
supporting
confidence: 63%
“…The advent of two-dimensional (2D) magnetic materials has attracted growing attention ranging from magnetics to quantum physics, resulting from the dimensionality and size effects on charge and spin correlation phenomena. However, most 2D magnetic materials have been focused on a few mother compounds exhibiting inherent 2D layer structures . To expand the diversity in chemical compositions and magnetic interactions at the 2D scale, it is highly desirable to create a universal strategy to artificially create 2D magnetic materials, particularly 2D molecular magnets with a variety of material groups and full tunability by external stimuli. The crystal structure transformation has been largely recognized as a key enabler for materials discovery. However, the structural transformations often occur between different lattice packings in the same dimensionality and have not been shown for the dimensionality transformation.…”
supporting
confidence: 63%
“…A transition metal with unfilled 3d shell electrons displays spin ordering at high temperatures and shows a novel spin reorientation transition (SRT) from in-plane to perpendicular magnetization as the film thickness increases. This unusual dependence of the magnetic behavior on the thickness is interpreted as a competition among the magnetoelastic volume anisotropy, the shape anisotropy, and the sum of the surface plus interface anisotropies due to the pseudomorphic growth. , Apart from the spin anisotropy modulated by the surface and the interface, an adsorbed layer (adlayer) on the transition metal can also modify the spin texture, i.e., spin polarization, spin ordering, or exchange coupling, to tune the magnetism. , Through the modification of the interface, the surface might alter the magnetic textures; it is thus important to clarify the magnetic texture near and beyond the region of pseudomorphic growth that makes a varied contribution to affect the magnetic response in the spintronics. On the other hand, tetracyano-based molecules such as TCNE and TCNQ have been known as promising organic materials to form metal–organic frameworks and organic/molecular magnets at room temperature for novel spintronic applications. Among these, the fluorinated counterpart of TCNQ, i.e., F4-TCNQ, is a strong acceptor molecule with high electron affinity, resulting in distinct charge transfer and hybridization states at the organic/metallic interface. , Previous studies revealed that superior magnetic coupling and significant spin polarization are induced at these ferromagnetic–organic heterojunctions. Based on these, we investigated an F4-TCNQ-tailored Ni surface in the present work to get more details of magnetization variation and how the magnetic coupling between F4-TCNQ and Ni films affects spin injection and transport at the organic–ferromagnetic interface.…”
Section: Introductionmentioning
confidence: 99%